Strategic Cloud Transformation in Banking - A Case Study of a Leading Czech Universal Bank - Doehring, William; Schönfeld, Jaroslav; Kuděj, Michal; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This thesis investigates strategic cloud transformation in the banking sector, using a selected Czech universal bank as a case study to explore how banks can effectively leverage cloud computing amidst regulatory, technological, and organizational complexities. Utilizing the Technology-Organization-Environment framework, the research employs qualitative analysis through semi-structured interviews and internal documentation. Results demonstrate substantial benefits, including enhanced operational efficiency, scalability, agility, resilience, and security improvements. However, findings indicate that legacy system complexities and regulatory compliance demands present significant adoption barriers. Ultimately, the thesis concludes that successful cloud transformation in banking necessitates a series of deliberate organizational and operational transformations, and proactive regulatory engagement.
Vedoucí práce: Jaroslav Schönfeld
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses